2021
DOI: 10.1101/2021.11.25.469998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KaKs_Calculator 3.0: calculating selective pressure on coding and non-coding sequences

Abstract: KaKs_Calculator 3.0 is an updated toolkit that is capable for calculating selective pressure on both coding and non-coding sequences. Similar to the nonsynonymous/synonymous substitution rate ratio for coding sequences, selection on non-coding sequences can be quantified as non-coding nucleotide substitution rate normalized by synonymous substitution rate of adjacent coding sequences. As testified on empirical data, it shows effectiveness to detect the strength and mode of selection operated on molecular seque… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To validate the accuracy of the identification of the subgenome, we concatenated all individual alignments of orthologous gene triplets headto-tail to form microchromosomes and build no-root trees using PHYLIP v3.69 (https://evolution.gs.washington.edu/phylip.html). Then, we calculated the Ks values using KaKs_Calculator v2.0 (Zhang, 2022) and analyzed the Ks distributions of P. hallii and the broomcorn millet subgenomes on nine chromosome sets, which confirmed that the identification of the subgenomes was accurate. The divergence time of the subgenomes was estimated using the Ó 2022 Society for Experimental Biology and John Wiley & Sons Ltd., The Plant Journal, (2023), 113, 787-801 distribution of Ks of the homologous genes with the formula T = Ks/2μ, where T is the divergence time, Ks is the peak value of the synonymous substitution rate and μ is the neutral mutation rate of the species.…”
Section: Subgenome Identification and Estimation Of Tetraploidization...mentioning
confidence: 68%
“…To validate the accuracy of the identification of the subgenome, we concatenated all individual alignments of orthologous gene triplets headto-tail to form microchromosomes and build no-root trees using PHYLIP v3.69 (https://evolution.gs.washington.edu/phylip.html). Then, we calculated the Ks values using KaKs_Calculator v2.0 (Zhang, 2022) and analyzed the Ks distributions of P. hallii and the broomcorn millet subgenomes on nine chromosome sets, which confirmed that the identification of the subgenomes was accurate. The divergence time of the subgenomes was estimated using the Ó 2022 Society for Experimental Biology and John Wiley & Sons Ltd., The Plant Journal, (2023), 113, 787-801 distribution of Ks of the homologous genes with the formula T = Ks/2μ, where T is the divergence time, Ks is the peak value of the synonymous substitution rate and μ is the neutral mutation rate of the species.…”
Section: Subgenome Identification and Estimation Of Tetraploidization...mentioning
confidence: 68%
“…The number of non‐synonymous substitutions per non‐synonymous site, dN, and the number of synonymous substitutions per synonymous site, dS, for each PDCoV S gene was calculated using NG, MS, GY‐HKY, and MA method in KaKs_Calculator 3.0 (Z. Zhang, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple sequence alignment within LFY a, LFY b and LFY c/d were performed with TranslatorX (Abascal et al, 2010) in combination with MUSCLE (Edgar, 2004), respectively. Pairwise Ka, Ks and Ka/Ks values were calculated using KaKs_Calculator 3.0 (Zhang, 2022).…”
Section: Methodsmentioning
confidence: 99%